Environmentalism in the Quran - Muflih Fahmi Kaunain (Resolusi: Jurnal Sosial Politik, 2018)
The complex interests of humanity have been increasing both in the quality and quantity. An environment with all its resources becomes the main source for humans to fulfill their needs. The basic need to continue living with nature becomes a global problem that should not have happened. The Quran as guidance in Islam has given a warning for all humanity to maintain the environment properly since it will have a good impact on humans themselves. The Quran with all the concepts and terminology about nature and environment shows that Islam is a friendly religion and even obliges its believers to live side by side and recognize natural behaviors properly because humans themselves will get the benefits. Islam as a religion carrying the message rahmatan lil alamin certainly does not exclude or specialize in spreading mercy to humans. It also includes all things in the universe. This paper tries to explain how the views of the Quran on the environment, which indeed provide space or special discussion about environmental safeguards. Thus humans, generally followers of religions and more specifically Muslim, can make religion not only the foundation of worship in the context of getting closer to God. Moreover, religion, in general, must also be able to provide a basic environmental view for its followers.